2018
DOI: 10.1093/cid/ciy1061
|View full text |Cite
|
Sign up to set email alerts
|

The Serogroup B Meningococcal Vaccine Bexsero Elicits Antibodies to Neisseria gonorrhoeae

Abstract: Background Neisseria gonorrhoeae and Neisseria meningitidis are closely-related bacteria that cause a significant global burden of disease. Control of gonorrhoea is becoming increasingly difficult, due to widespread antibiotic resistance. While vaccines are routinely used for N. meningitidis, no vaccine is available for N. gonorrhoeae. Recently, the outer membrane vesicle (OMV) meningococcal B vaccine, MeNZB, was reported to be associated with reduced rates of gonorrhoea following a mass vacc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
142
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(151 citation statements)
references
References 48 publications
(87 reference statements)
4
142
0
5
Order By: Relevance
“…A retrospective case-control study estimated a vaccine effectiveness of 31% in preventing gonorrhea infection among fully vaccinated 15-30-year-olds (Petousis-Harris et al, 2017), showing the potential of OMV vaccines to reduce the incidence of gonorrhea. In addition, other non-OMV components of 4CMenB could further contribute to cross-protection, in particular NHBA, which is highly conserved across gonococcal strains (Comanducci et al, 2002;Hadad et al, 2012;Semchenko et al, 2018). Given growing concerns relating to gonococcal infections and the threat of antimicrobial resistance, any disease reduction attributable to 4CMenB use would be highly desirable from a public health perspective.…”
Section: Potential For 4cmenb To Offer Protection Beyond Menb Diseasementioning
confidence: 99%
“…A retrospective case-control study estimated a vaccine effectiveness of 31% in preventing gonorrhea infection among fully vaccinated 15-30-year-olds (Petousis-Harris et al, 2017), showing the potential of OMV vaccines to reduce the incidence of gonorrhea. In addition, other non-OMV components of 4CMenB could further contribute to cross-protection, in particular NHBA, which is highly conserved across gonococcal strains (Comanducci et al, 2002;Hadad et al, 2012;Semchenko et al, 2018). Given growing concerns relating to gonococcal infections and the threat of antimicrobial resistance, any disease reduction attributable to 4CMenB use would be highly desirable from a public health perspective.…”
Section: Potential For 4cmenb To Offer Protection Beyond Menb Diseasementioning
confidence: 99%
“…The current Bexsero N. meningitidis serogroup B vaccine contains recombinant proteins which may provide additional cross-protection for N. gonorrhoeae, particularly the NHBA peptide which is the only one known to be surface exposed (238). Our results show that there were several NHBA peptides found in the top 10 N. gonorrhoeae strains in Australia.…”
Section: Vaccine Peptidesmentioning
confidence: 73%
“…Although that particular vaccine is no longer available, the vaccine components are included in the current Bexsero vaccine which also contains additional recombinant proteins including NHBA, factor H binding protein (fHbp) and Neisseria adhesion A (NadA) (251). Of these, NHBA appears to be the only one which is surface exposed, making a viable target for vaccine efficacy (238). Semchenko et al (238) showed that NHBA is well conserved among N. gonorrhoeae and that three NHBA variants (475, 481 and 542), which were also found in our top 10, account for a large majority of N. gonorrhoeae isolates found in the pubMLST database and noted cross-reactivity for NHBA in both N. gonorrhoeae and N.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations